VLBI observations of a sample of Palomar–Green quasars – I. Parsec-scale morphology. Issue 1 (28th October 2022) - Wang, Ailing; An, Tao; Cheng, Xiaopeng; Ho, Luis C; Kellermann, Kenneth I; Baan, Willem A; Yang, Jun; Zhang, Yingkang
ABSTRACT: We observed 20 Palomar–Green quasars at low redshift ( z < 0.5) with total flux density >1 mJy, including four radio-loud quasars (RLQs) and 16 radio-quiet quasars (RQQs), using the Very Long Baseline Array (VLBA) at 5 GHz. 10 RQQs are clearly detected in the VLBA images, and a compact radio core is identified in eight of them, indicating the prevalence of active galactic nucleus (AGN)-related radio emission in this flux-density-limited RQQ sample. The RQQs and RLQs in our sample have a division at ∼30 mJy. The radio emission from RQQs appears to be the result of a combination of star formation and AGN-associated activities. All RQQs in our sample have a 5 GHz flux density ratio of Very Large Array (VLA) A-array to D-array $f_{\rm c} = S_{\rm A}^{\rm VLA}/S_{\rm D}^{\rm VLA}$ above 0.2. The RQQs with fa (VLBA and VLA flux density ratio $S^{\rm VLBA}/S_{\rm A}^{\rm VLA}) \gt 0.2$ versus fa < 0.2 show significant differences in morphology, compactness, and total flux density. f a of RQQs is systematically lower than that of RLQs, probably due to the extended jets or relic jets of RQQs on tens to hundreds parsecs that are resolved out in VLBA images. Future larger samples, especially with the addition of milliarcsec resolution radio images of RQQs with total flux densities below 1 mJy, can test the conclusions of this paper and contribute to the understanding of the radio emission mechanism of RQQs, and the dichotomy and physical connection between RQQs and RLQs.